1999
DOI: 10.1038/sj.ijo.0800961
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index (weight/height2) or percentage body fat by bioelectrical impedance analysis: which variable better reflects serum lipid profile?

Abstract: We present population data on percentage body fat (%BF) by bioelectrical impedance analysis (BIA) in 12 287 men and 6657 women aged 30 ± 69 y. In addition, we examined relationships among BMI, %BF and serum lipids (totalcholesterol (TC), HDL-cholesterol (HDLC), TCaHDLC ratio, LDL-cholesterol (LDLC) and triglycerides (TG)) in order to determine whether body mass index (BMI, kgam 2 ) or %BF by BIA better re¯ected lipid metabolism. Women had larger %BF than men in all age groups. On the other hand, women aged`60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
3
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 4 publications
4
49
3
6
Order By: Relevance
“…This observation is in line with previous studies, [8][9][10][11][12] but contrary to others. [13][14][15] However, in all these studies, [8][9][10][11][12][13][14][15] %FM was determined by the use of bioelectrical impedance analysis. Thus, the inaccuracies of impedance measurements may add to the observed discrepancies.…”
Section: Value Of Fm Vs Anthropometric Obesity Indices For Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is in line with previous studies, [8][9][10][11][12] but contrary to others. [13][14][15] However, in all these studies, [8][9][10][11][12][13][14][15] %FM was determined by the use of bioelectrical impedance analysis. Thus, the inaccuracies of impedance measurements may add to the observed discrepancies.…”
Section: Value Of Fm Vs Anthropometric Obesity Indices For Assessmentmentioning
confidence: 99%
“…7 However, studies comparing the values of BMI and %FM in the prediction of metabolic risk are contradictory. [8][9][10][11][12][13][14][15] Some authors found that when compared to %FM BMI was similar or even more closely associated to cardiovascular risk factors, for example, lipid profile, blood pressure or insulin resistance (IR). [8][9][10][11][12] By contrast, the value of %FM exceeded BMI in other studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vários estudos têm mostrado que o IMC apresenta boa correlação com a quantidade de gordura corporal determinada por medidas diretas como densitometria 11 , bioimpedância elétrica (BIA) 12 , pregas cutâneas 11,13 , relação cintura/quadril (RCQ) 14 e circunferência da cintura (CC) 15 .…”
Section: íNdice De Massa Corporalunclassified
“…is subgroup was called in the literature as "occult obese 24 . We veri ed this subgroup (occult obese) had a stronger correlation with a blood pressure and lipoprotein fractions HDL-c, TG, VLDL-c.…”
Section: Resultsmentioning
confidence: 99%